Not a very NEET solution : representing problematic labour market transitions among early school-leavers - Furlong, Andy [Verfasser] (My University, 2006)
"Concern with youth unemployment has been replaced with a focus on those not in education, in employment, or in training (NEET). With current levels of youth unemployment low, this emphasis helps remind us that an increase in employment levels is not necessarily accompanied by a reduction in vulnerability. While NEET can be used as a concept for representing problematic transitions, it is an ill-considered concept that places an undue and often misleading emphasis on voluntarism. Drawing on the Scottish School Leavers Survey, the article explores the policy implications of different definitions of NEET, highlights its prevalence, and examines the characteristics of those who are NEET. It is argued that to represent vulnerable youth effectively we must either use a set of definitions that are narrower than that represented by NEET, or adopt a much broader definition that provides a basis for more far-reaching interventions." (author's abstract, IAB-Doku) ((en))
Keywords: G 1.3.2 Bildungsverhalten und -verläufe; P 2.1.1 Ohne Schulabschluss; I 2.2.1 Westeuropa; Schulabbrecher; Schulabbruch; Großbritannien